Similar response patterns to topical minoxidil foam 5% in frontal and vertex scalp of men with androgenetic alopecia: a microarray analysis. (1st June 2015) - Mirmirani, P.; Consolo, M.; Oyetakin‐White, P.; Baron, E.; Leahy, P.; Karnik, P.
Summary: Background: There are regional variations in the scalp hair miniaturization seen in androgenetic alopecia (AGA). Use of topical minoxidil can lead to reversal of miniaturization in the vertex scalp. However, its effects on other scalp regions have been less well studied. Objectives: To determine whether scalp biopsies from men with AGA show variable gene expression before and after 8 weeks of treatment with minoxidil topical foam 5% (MTF) vs. placebo. Methods: A placebo‐controlled double‐blinded prospective pilot study of MTF vs. placebo was conducted in 16 healthy men aged 18–49 years with Hamilton–Norwood type IV–V thinning. The subjects were asked to apply the treatment (active drug or placebo) to the scalp twice daily for 8 weeks. Stereotactic scalp photographs were taken at the baseline and final visits, to monitor global hair growth. Scalp biopsies were taken at the leading edge of hair loss from the frontal and vertex scalp before and after treatment with MTF and placebo, and microarray analysis was performed using the Affymetrix GeneChip HG U133 Plus 2.0. Results: Global stereotactic photographs showed that MTF induced hair growth in both the frontal and vertex scalp of patients with AGA. Regional differences in gene expression profiles were observed before treatment. However, MTF treatment induced the expression of hair keratin‐associated genes and decreased the expression of epidermal differentiation complex and inflammatory genes in both scalp regions. Conclusions: These data suggest that MTF is effective in the treatment of both the frontal and vertex scalp of patients with AGA.